Evaluation of photobiomodulation therapy associated with guided bone regeneration in critical size defects. In vivo study (Journal of Applied Oral Science, 2022)
The repair of bone defects raises the interest of investigators in several health specialties. Grafting techniques with bone substitutes and laser therapies have been investigated to replace autogenous bone and accelerate the bone healing process. Objective: To evaluate the effect of photobiomodulation therapy (PBMT) associated with guided bone regeneration (GBR) in critical size defects. Material and Methods: The study was conducted on 80 male rats (Rattus norvegicus albinus, Wistar) submitted to surgical creation of a critical size defect on the calvaria, divided into eight study groups: group C (control - only blood clot); group M (collagen membrane); group PBMT (photobiomodulation therapy); group AB (autogenous bone); group AB+PBMT; group AB+M; group PBMT+M; group AB+PBMT+M. The animals were killed 30 days postoperatively. After tissue processing, bone regeneration was evaluated by histomorphometric analysis and statistical analyses were performed (Tukey test, p<0.05). Results: All groups had greater area of newly formed bone compared to group C (9.96±4.49%). The group PBMT+M (achieved the greater quantity of new bone (64.09±7.62%), followed by groups PBMT (47.67±8.66%), M (47.43±15.73%), AB+PBMT (39.15±16.72%) and AB+PBMT+M (35.82±7.68%). After group C, the groups AB (25.10±16.59%) and AB+M (22.72±13.83%) had the smallest quantities of newly formed bone. The area of remaining particles did not have statistically significant difference between groups AB+M (14.93±8.92%) and AB+PBMT+M (14.76±6.58%). Conclusion: The PBMT utilization may be effective for bone repair, when associated with bone regeneration techniques.